A family medicine case report of uncontrolled grade 2 hypertension in MRS. A - Devin Budijono; Novendy Novendy; Valeria Saputra; Hartati Hartati (Institute of Computer Science (IOCS), 2023)
Hypertension is a condition in which systolic blood pressure is ≥ 140 mmHg and/or diastolic blood pressure is ≥ 90 mmHg after repeated measurements in a clinic or health care facility. Based on the results of RISKESDAS in 2018, Banten Province has a prevalence of hypertension amount 29.4%. Based on data at the Kresek Health Center in July-December 2021 which mentioned that hypertension was the disease with the most cases in the working area of the Kresek Primary Health Centerv(Puskesmas). In order to assess the problem, this study used the family medicine approach and the Mandala of Health as the problem assessment to determine the factors that cause uncontrolled hypertension. A 66-year-old woman came to Kresek Puskesmas with hypertension since 6 years ago. The patient has complaints of pain all over the head. She claimed routinely take drugs prescribed by the Puskesmas, but not routinely control blood pressure. Thus, blood pressure is still not controlled. After the intervention, the patient's complaints became reduced and her blood pressure decreased from 160/100 to 140/90. In addition, she obtained a family understanding of hypertension, factors that cause uncontrolled hypertension, as well as complications that can occur due to hypertension. The discovery of factors caused uncontrolled hypertension in patients. It is expected that she can improve her lifestyle to be better so that complications from hypertension do not occur.